Minsky's financial fragility: An empirical analysis of electricity distribution companies in Brazil (2007-15) - Ernani Teixeira Torres Filho; Norberto Montani Martins; Caroline Yukari Miaguti (Levy Economics Institute of Bard College, 2017)
The present paper applies Hyman P. Minsky's insights on financial fragility in order to analyze the behavior of electricity distribution companies in Brazil from 2007 to 2015. More specifically, it builds an analytical framework to classify the firms operating in this sector into Minskyan risk categories and assess how financial fragility evolved over time, in each firm and in the sector as a whole. This work adapts Minsky's financial fragility indicators and taxonomy to the conditions of the electricity distribution sector and applies them to regulatory accounting data for more than 60 firms. This empirical application of Minsky's theory for analyzing firms engaged in the provision of public goods and services is a novelty. The results show an increase in the financial fragility of those firms (as well as the sector) throughout the period, especially between 2008 and 2013, even though the number of firms operating at the highest level of financial risk hardly changed.
Keywords: G31; G38; H40; L59; L94; 330; Minsky; Financial Fragility; Financial Instability Hypothesis; Electricity Distribution Companies